DAYA TERIMA KONSUMEN TERHADAP BAKPAO YANG DIPERKAYA SIFAT FUNGSIOAL SERAT DAN ANTIOKSIDAN BERBASIS DAUN KELOR (Moringa oleifera) - Darmawan, Eman (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2017)
The research was designed to determine the effect of substitution of Moringa leaves to the level of consumer acceptance ofÂ  bun product and nutrient content. This research uses a completely randomized design (CRD) with single consisted Moringa leaf flour substitution (0%, 5%, 10%, 15%, 20%), each treatment replicated 3 times. Data were analyzed using analysis of variance (ANOVA), if there was a difference between the treatment, it would analyze with Duncan`s Multiple Ranges Test Method (DMRT) at the level of 5%. The addition of Moringa leaf affect the organoleptic properties of bun product, the color of the bun was green, tasted moringa leaves, while the texture of buns increases softly. Based on organoleptic parameters, then the addition of Moringa leaves are preferred by the panelists was the addition of Moringa leaves as much as 10% with a score of 3.85, Reseda (3.3), a rather tasted the leaves of Moringa (3.35), soft texture (3.85 ), 36.78% water, 0.09% chlorophyll, fiber 14.98%, and 43.48% antioxidant activity.Â